Effect of Price Discounts on Consumer Purchase Satisfaction (Study at Indomaret Majene Branch) - Zulkifli Zulkifli (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
The purpose of this study is to determine the effect of discounted prices on Customer Purchase Satisfaction at Indomaret Majene Branch.This research was conducted at Indomaret Majene branch, Majene Regency, namely the researcher wanted to know howabout influencediscounted prices for Customer Purchase Satisfaction Indomaret Majene BranchThe data analysis technique used is a simple linear regression test. The results showed that the price discount variable had a positive and significant effect on the consumer purchase satisfaction variable at the Majene branch of Indomaret.